The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1755-1315/302/1/012149
|View full text |Cite
|
Sign up to set email alerts
|

Problems of preservation of prehistoric cultural heritage objects in the Arctic

Abstract: Problems of preservation and research of prehistoric cultural heritage objects in the Arctic are reviewed in the article. To determine the priority tasks in the field of preserving the heritage of this region, the most probable risks of physical loss and loss of quality of objects associated with natural and anthropogenic factors are analyzed. A special feature of the Arctic is its increased sensitivity to anthropogenic influence and climate change. Therefore, in the context of global warming, the risks of los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The concept was confirmed and developed in studies of rock carvings of the labyrinths located in the Caucasus. The navigational concept is consistent with the characteristics of earlier objects -the location of natural/man-made zoo-and anthropomorphic sculptures on ancient routes and the orientation of megalithic complexes [3,4,5].…”
Section: Introductionsupporting
confidence: 64%
“…The concept was confirmed and developed in studies of rock carvings of the labyrinths located in the Caucasus. The navigational concept is consistent with the characteristics of earlier objects -the location of natural/man-made zoo-and anthropomorphic sculptures on ancient routes and the orientation of megalithic complexes [3,4,5].…”
Section: Introductionsupporting
confidence: 64%
“…sea-level rise, erosion, permafrost thaw) and other human impacts (e.g. development, extractive industries) (Amand et al, 2020;Anderson et al, 2017;Blankholm, 2009;Bourgeois et al, 2007;Hilton 2018;Hollesen et al, 2016Hollesen et al, , 2017Hollesen et al, , 2018Marsadolov et al, 2019). Archaeological sites are important for many reasons.…”
Section: Archaeological Sitesmentioning
confidence: 99%
“…Archaeological sites are important for many reasons. For example, they can be used as proxy records for accurately reconstructing past environments (Amand et al, 2020), for understanding historical social and cultural relations (Andrews et al, 2016; Hollesen et al, 2016; Marsadolov et al, 2019), and they are part of the rich tapestry of cultures’ history and continuity, identity, knowledge and sense of place (Carmichael et al, 2018; Fotoric and Seekamp, 2017, 2019; Hollesen et al, 2018). Anderson et al (2017) suggested that a one metre rise in sea level will result in the loss of >13,000 recorded archaeological sites in the south-eastern part of the United States of America (USA) alone.…”
Section: Archaeological Sitesmentioning
confidence: 99%
“…These driving forces are critical in determining the rate, amount, and direction of growth. Similar research in other developing countries, [30,32,33,34] yielded an initial tentative list of 11 driving forces forming US and LULC change.…”
Section: Methodsmentioning
confidence: 87%